Peach palm core collection in Brazilian Amazonia - Cristo-Araújo,Michelly de (2015)
The Peach palm Active Germplasm Bank has abundant genetic diversity in its holdings. Because it is a live collection, maintenance, characterization and evaluation are expensive, restricting its use. One way to promote more efficient use is to create a Core Collection, a set of accessions with at least 70% of the genetic diversity of the full collection with minimal repetition. The available geographic, molecular marker (RAPD) and morphometric information was systematized and the populations were stratified into wild and domesticated. The Core Collection consists of 10% of the entire collection: 31 accessions of landraces, 5 accessions of non-designated populations and 4 accessions of wild populations. The Core has 92% of the molecular polymorphism and 95% of the heterozygosity of the full collection, with minimal divergence between them by molecular variance. The Core is already receiving priority maintenance, which will contribute to long term conservation.